Hábitos alimentares na perspectiva da Geografia: os sabores em Guarani de Goiás - Passos, Lisandra Lavoura Carvalho (2008)
The present work is result of the nearness between geography and food and, aim the manners of eat in a context of reality like possibility of geographical investigation. It moderator for the man and your relations with the nature, with the social circle, with the people and with the place, to come into of production s manners of foods offered to know the relation of the men with the nature, the your organization social space and your relations with others actors, in the first chapter, we looked for the theorical fundamentation, finding in the cultural geography, the dialogue necessary to settle the categories of place, lived space, representations, food habits and support it. The register of cities of small region of Vão do Paranã in the goiano northeast and the informations of permanent and temporary farm works, having like prominent the city Guarani de Goiás made present. The second chapter, the confrontation between theory and practical beginning empirically the grasp of the manners of eat of the group in the city Guarani de Goiás, trying to explain the meanings of symbolic nature in the cycle of plant, pick, prepare and eat the foods. In the manners of prepare the foods made mister a space preparation of the food, in it the possibility of observe the scene pursued the social relations that established by means of food. In this space stressing the woman like main actress, understanding that she is producing and keeping of feed traditions and consequently cultural traditions in group in that is inserted. For that reason this dialogue between the make hers and the our interpretation, that allow to notice the beat, the auto sufficiency of foods, the relations, and the interior and external conflict that .The third chapter, reproduce the event mutirão of cassava´s flour and the production of rapadura, focusing in yours similarities, and differences, activities that cross and manifest values and identities local. The reflection about food brought the necessity of reflect too the hunger, like form of become it discussable. Clipping too was dedicated the participation of Brazil Kitchen a movable course of feed education, that multiply the concept of healthy and hygienic food. To deduce and interpret a city Guarani de Goiás one of municipal of goiano northeast was evidenced a municipal district segregated and conflict, however, a city that is a place of existence and the reproductions of men s life that like any human vacuum evolutions and opportunities.